Anti-apolipoprotein A-1 auto-antibodies as active modulators of atherothrombosis - Pagano, Sabrina; Carbone, Federico; Burger, Fabienne; Roth, Aline; Bertolotto, Maria; Pane, Bianca; Spinella, Giovanni; Palombo, Domenico; Pende, Aldo; Dallegri, Franco; Satta, Nathalie; Virzi, Julien; Fontana, Pierre; Mach, François; Montecucco, Fabrizio; Vuilleumier, Nicolas (Thrombosis and Haemostasis, 2016)
Humoral autoimmune-mediated inflammation plays a role in atherogenesis, and potentially in arterial thrombosis. Anti-apolipoprotein A-1 (apoA-1) IgG have been reported to represent emergent mediators of atherogenesis through Toll-like receptors (TLR) 2, 4 and CD14 signalling. We investigated the role of anti-apoA-1 IgG on tissue factor (TF) expression and activation, a key coagulation regulator underlying atherothrombosis. Atherothrombosis features were determined by immunohistochemical TF staining of human carotid biopsies derived from patients with severe carotid stenosis undergoing elective surgery (n=176), and on aortic roots of different genetic backgrounds mice (ApoE-/-; TLR2-/-ApoE-/- and TLR4-/-ApoE-/-) exposed to passive immunisation with anti-apoA-1 IgG. Human serum levels of anti-apoA-1 IgG were measured by ELISA. In vitro, on human-monocyte-derived-macrophages (HMDM) the anti-apoA-1 IgG increased TF expression and activity were analysed by FACS and chromogenic assays in presence of different pharmacological inhibitors. Human serum anti-apoA-1 IgG levels significantly correlated to intraplaque TF expression in carotid biopsies (r=0.31, p<0.001), which was predictive of clinically symptomatic lesions. On HMDM, anti-apoA-1 IgG induced a TLR2, 4 and CD14-dependent increase in TF expression and activity, involving NF-kappaB and a c-Jun N-terminal kinase-dependent AP-1 transcription factors. In ApoE-/- mice, anti-apoA-1 IgG passive immunisation significantly enhanced intraplaque TF expression when compared to control IgG. This effect was lost in both TLR2-/-ApoE-/- and TLR4-/-ApoE-/- mice. These results demonstrate that anti-apoA-1 IgG are associated with TF expression in human atherosclerotic plaques, induce TF expression in vitro and in vivo through TLR2 and 4 signalling, supporting a possible causal relationship between anti-apoA-1 IgG and atherothrombosis.
Keywords: Anti-apoA-1 IgG; tissue factor; atherothrombosis; macrophages; toll-like receptors